Correlation of granulin expression in intracranial meningiomas to clinical parameters - KIM, CHOONG HYUN (D.A. Spandidos, 2010)
The granulins, a novel class of peptides from leukocytes, are growth factors that mediate cycle progression and the motility of epithelial and mesenchymal cells. They are also involved in tissue repair and tumorigenesis. We investigated granulin expression in intracranial meningiomas by reverse transcription-polymerase chain reaction and correlated its expression to clinical parameters. Seventy-nine patients who underwent tumor removal for intracranial meningiomas were included in this study. Granulin expression was analyzed in respect to clinical parameters including age, gender, tumor size and peritumoral brain edema (PTBE). Granulin was expressed in the tumors of 29 of 79 (36.7%) patients with intracranial meningiomas, and its presence or absence was correlated to tumor size and PTBE volume. However, granulin expression did not vary significantly according to patient age or gender. Our data provide improved understanding about the clinical implications of granulin expression in intracranial meningiomas. Additionally, our information suggests a potential role for granulin as a molecular target in the management of meningiomas.